Penerapan Relaksasi Otot Progresif Terhadap Penurunan Tingkat Kecemasan pada Pasien Luka Kaki Diabetik - Kharisma Nur Armadhani; Irma Mustika Sari (Vitamin : Jurnal ilmu Kesehatan Umum, 2024)
Background: Diabetic foot ulcers are one of the most common complications in patients with diabetes mellitus. Patients with diabetic foot wounds have various degrees of anxiety. One of the anxiety measurement tools is HARS (Hamilton Anxiety Rating Scale). Progressive muscle relaxation is one of the non-pharmacological treatments to reduce anxiety. Objective: To describe the results of the implementation of progressive muscle relaxation on anxiety levels in patients with diabetic foot wounds. Methods: This study used a descriptive research design case study approach by observing the anxiety level of diabetic foot wound patients on 2 respondents, carried out in the morning and evening for 5 consecutive days with a frequency of 15 minutes. The instruments used were HARS (Hamilton Anxiety Rating Scale) scale sheet, SOP (Standard Operating Procedure) progressive muscle relaxation, anxiety level observation sheet, stopwatch. Results: Results: There were changes in anxiety levels before and after progressive muscle relaxation in Mrs. S from moderate (27) to mild (15). While in Mrs. I from moderate (26) to mild (15). Conclusion: The application of progressive muscle relaxation can be useful for reducing anxiety levels in both diabetic foot wound patients.